MODERN COMPUTER TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF GYNECOLOGICAL DISEASES: ROLE AND SIGNIFICANCE - Atakhanov Sanjarbek Anvarovich; Mirzayeva Mokhchekhra Mashhurjon qizi (Bright Mind Publishing, 2025)
In recent years, gynecological diseases have significantly increased worldwide, becoming a serious problem linked to lifestyle and environmental factors. This article discusses the types of gynecological diseases, their causes, diagnostic methods, treatment approaches, and their impact on women’s health. The role of modern information technologies in the diagnosis and treatment of such diseases is also highlighted. Digital technologies allow early detection, development of effective treatment strategies, and improvement of healthcare quality.
Keywords: Gynecological diseases, artificial intelligence, telemedicine, early diagnosis, electronic medical records, cyst, computed tomography, ultrasound.